John Paul II and Benedict XVI’s concern for the protection of the faithful against the most serious crimes, with particular emphasis on the sexual abuse of minors committed by clergy - Bartosz Trojanowski (Polonia Sacra)
The problem of dealing justly and efficiently with the most serious crimes in the Church after the promulgation of the Code of Canon Law in 1983 became the concern of Cardinal Joseph Ratzinger, later Benedict XVI, and John Paul II. Their cooperation and the decisions of Benedict XVI, as a continuation of the path started, laid the foundations for the creation of a system of canonical criminal law capable of responding properly and effectively to the most serious crimes committed by the faithful in the Church. The introduction of a clear scope of competence for the Congregation for the Doctrine of the Faith, the definition of a longer limitation period, the possibility of revoking it, the centralization of procedural steps, entrusting them to qualified personnel, enabling the control of the action of individual superiors are very concrete legal solutions that confirm the teaching of the Church and the definite statements of the two Popes on the protection of the most vulnerable in the Church from the immense harm of sexual abuse that some clerics could commit against them. The article presents and discusses concrete legal solutions and relates them with the teachings and attitudes of the two popes towards protecting minors in the Church. It is an attempt to argue for the defense of their good names and to oppose the unfounded accusations made against these two authorities.